Preliminary studies on the use of sugar cane bagasse ash (SCBA) in the manufacture of alkali activated binders - Castaldelli, V. N. [UNESP]; Tashima, M. M.; Melges, J. L. [UNESP]; Akasaki, J. L. [UNESP]; Monzó, J.; Borrachero, M. V.; Soriano, L.; Payá, J. (Trans Tech Publications, 2014)
Alkali activated binders require the addition of a mineral-rich amorphous silica and alumina. This paper proposes the use of a mineral residue from the burning of sugar cane bagasse. The alkali activated mixtures were prepared containing binary mixtures of sugar cane bagasse ash (SCBA) and other mineral admixtures: fly ash (FA) or blast furnace slag (BFS). As alkaline activators, mixtures of alkali (Na+ or K+) hydroxide and alkali (Na+ or K+) silicate were used. Alkali-activated pastes and mortars containing binary systems SCBA/FA or SCBA/BFS were prepared and cured at 65 °C. Microstructural properties of these alternative binders were assessed by means of TGA, SEM, XRD and pH measurements. Mechanical strength of mortars was performed after 3 and 7 days at 65 °C. Compressive mechanical strengths of these mortars were in the range 30-55 MPa, showing the good mechanical performance achieved by the alkali activation. Microstructural studies suggested the development of stable matrices and the formation of typical gel. © (2014) Trans Tech Publications, Switzerland.
Keywords: Alkali activation; Mechanical strength; Microstructure; Sugar cane bagasse ash (SCBA)